Usada Bali-Based Self-Management in Type 2 Diabetes - Adiswarya Putri, Made Pradnyandari; Permatahati Wiguna, Nyoman I Intan; Narayani, Ni Made Rahajeng Ayu; Pratiwi, Putu Elfira; Sutayani, Luh Putu Prema; Wijaya, I Gede Satria Dharma (Fakultas Ilmu Kesehatan, 2025)
Type 2 diabetes is a growing global health problem, especially in low- and middle-income countries. Poor self-management remains a major barrier to good blood sugar control. In Bali, traditional practices known as Usada Bali may support diabetes self-management. This study aimed to review Usada Bali–based self-management approaches for patients with type 2 diabetes. A literature review was conducted using PubMed and Google Scholar. Articles published between 2016 and 2024 were selected based on relevance to diabetes self-management, Balinese culture, herbal medicine, yoga, spiritual healing, and family-based support. Data were analyzed using a narrative synthesis approach. The findings showed that Usada Bali practices, including herbal drinks (loloh), traditional diet, yoga, foot massage, spiritual healing, and family involvement, were associated with improved blood glucose control, reduced anxiety, better insulin sensitivity, and enhanced self-management behavior. Integrating cultural and spiritual elements into diabetes care may increase patient acceptance, adherence, and long-term lifestyle changes. However, more clinical studies are needed to strengthen scientific evidence and standardize interventions.